Pengaruh Kualitas Produk, Harga Dan Promosi Terhadap Keputusan Pembelian Konsumen Pada Online Shop Bukalapak (Studi Kasus Mahasiswa Feb Angkatan 2016 Universitas Islam Malang) - Heriyanto Heriyanto; N. Rachma; Siti Asiyah (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study was conducted to determine the effect of product quality, price and promotion on purchasing decisions of online shop consumers on the Buk netbook of 2016 FEB students, Islamic University of Malang. This research uses explanatory research and a quantitative approach. This study uses a population of 700 based on the number of students from the Faculty of Economics and Business class 2016, Malhotra Theory is used to take a sample consisting of 17 question items so the samples obtained in this research are 85 respondents (17 question items x 5).To solve the problem in this study, using the validity test, reliability test, normality test, multiple linear regression test, multicollinearity test, heteroscedasticity test, classical assumption test. The research uses multiple linear regression analysis with the help of SPSS 16. The results of this study are that the variables of product quality, price and promotion influence purchasing decisions simultaneously, while partially the variables of product quality, price and promotion affect purchasing decisions at the online shop Bukalapak on FEB students class 2016 University Islam Malang. Keywords: Product Quality, Price, Promotion and purchase decisions